Avaliação dos monócitos de pacientes com Leishmaniose Tegumentar Americana antes e após o tratamento - Veras, Poliana Ribeiro Valadares (2015)
American tegumentary leishmaniasis (ATL) is an infectious parasitic disease caused by Leishmania protozoa. The disease presents as cutaneous leishmaniasis (CL) and mucosal leishmaniasis (ML). The mechanisms of the immunopathogenesis and infection control are not yet fully understood, and monocytes can be involved in these mechanisms. The monocytes are divided into three subsets (CD14hiCD16-, classical monocytes; CD14hiCD16+, the intermediates; and CD14loCD16+ non- classical) and are the major cell producing cytokines in peripheral blood.The objective of this study was to assess possible alterations in the percentages of monocytes subsets; and in the tumor necrosis factor (TNF) and interleukin 10 (IL -10) production in whole blood cultures from patients with CL and ML, before and after treatment. Peripheral blood from patients (n = 54; 31 CL and ML 23) and controls (n = 54) was used to identify monocytes by flow cytometry and for whole blood cultures. The blood was incubated in the absence (medium) or presence of toll-like receptor agonists (Pam3Cys and LPS for TLR2 and TLR4, respectively) or L. (V.) braziliensisantigens (AG) to assess TNF and IL-10. Cytokines were quantified by enzyme-linked immunosorbent assay (ELISA).The results showed an increase in the percentage of CD16+ monocytes, especially CD14loCD16+monocyte subset in CL patients, but not in ML, before treatment (p <0.05). After treatment, the percentages of these monocytes in CL patients back to similar levels of those from healthy individuals. In patients with ML, there was also a reduction in the percentages of CD16+ monocytes after treatment. The production of TNF and IL-10 was not significantly altered in whole blood cultures from patients, compared with those from healthy controls. Among the stimuli used, only the AG did not induce significant amounts of IL-10 in whole blood cultures from patients. After treatment, TNF concentrations decreased in CL whole blood cultures, except when the stimulus was Pam3Cys (TLR2), which induced an increase in TNF levels (p <0.05). In ML whole blood cultures no significant differences were detected between the concentrations of TNF and IL-10 produced before and after treatment.The IL-10 concentrations were not significantly altered after treatment of CL patients. The data indicate that percentages of CD16+ monocytes are increased in CL. Also, they suggest that monocytes from patients with CL or ML show a decreased capacity to produce IL-10 in response to AG, what can hamper the control of the inflammatory response. The data also suggest that the ability of monocytes to be activatedthrough TLR2 can be suppressed in CL what isrecovered after treatment. An analysis of TLR2 and TLR4 in monocytes from patients with ATL can improve the knowledge about cytokine induction in these cells.